2020
DOI: 10.3390/lubricants8010010
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of SiO2 and TiO2 Nanoparticles as Lubricant Additives in Sunflower Oil

Abstract: In recent years, there has been growing concern regarding the use of petroleum-based lubricants. This concern has generated interest in readily biodegradable fluids such as vegetable oils. The present work evaluated the rheological and tribological characteristics of sunflower oil modified with silicon dioxide (SiO2) and titanium dioxide (TiO2) nanoparticles as lubricant additives at different concentrations. A parallel plate rheometer was used to evaluate the effects of concentration and shear rate on the she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 31 publications
4
39
0
1
Order By: Relevance
“…One of the approaches to reducing friction in a boundary lubrication regime is the use of a dilute solution of saturated fatty acids (palmitic and stearic acid) in vegetable oils [ 20 , 21 , 22 ]. Cortes et al [ 23 ] evaluated the tribological characteristics of sunflower oil modified with titanium dioxide and silicon dioxide nanoparticles as lubricant additives. It was found that the rheological behavior of the sunflower-based lubricant is dependent on the type and concentration of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…One of the approaches to reducing friction in a boundary lubrication regime is the use of a dilute solution of saturated fatty acids (palmitic and stearic acid) in vegetable oils [ 20 , 21 , 22 ]. Cortes et al [ 23 ] evaluated the tribological characteristics of sunflower oil modified with titanium dioxide and silicon dioxide nanoparticles as lubricant additives. It was found that the rheological behavior of the sunflower-based lubricant is dependent on the type and concentration of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…sin cos sin 1 sin π sin sin (11) Concerning the e/h expression of ellipsoidal nanoparticle in the lubrication system, e/h is related to γ, θ, αθ, and β (as displayed in the list of symbols) in parametric expression. In Fig.…”
Section: Discussion Of E/h Expressionmentioning
confidence: 99%
“…Different types of nanoparticles, such as metal, metal oxide, metal carbonate, fullerenes, silica, and carbon compound, have been developed as solid lubricants and lubricant modifiers for friction modification and wear resistance [3,[6][7][8][9][10][11][12][13][14]. The tribological properties of metal nanoparticle additives (like Fe, Cu, Ni, and Co) in base lubricants indicate that they play a significant role in decreasing friction and wear by forming a tribo-layer [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional lubricants are composed of base oil and additives conferring specific properties to the lubricant. Friction reduction additives are used to ensure the lubricating properties in the friction boundary regime [1][2][3][4][5]. Other additives act on the oiliness of the lubricant [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%